Association of Systemic Inflammation Response Index with Short-Term All-Cause Mortality in Decompensated Liver Cirrhosis Patients - Cheng J; Ju H; Wang G; He C; Wang W (Journal of Inflammation Research)
Jin Cheng,1,* Honglei Ju,1,* Guixiang Wang,2,* Chiyi He,1 Wei Wang1 1Department of Gastroenterology, Yijishan Hospital of Wannan Medical College, Wuhu, People’s Republic of China; 2Department of Gastroenterology, The Second Affiliated Hospital of Wannan Medical College, Wuhu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Wang, Department of Gastroenterology, Yijishan Hospital of Wannan Medical College, No. 2, Zheshan West Road, Wuhu, Anhui Prov, 241000, People’s Republic of China, Email wwwy@wnmc.edu.cnBackground: The Systemic Inflammation Response Index (SIRI) has demonstrated predictive capabilities for clinical outcomes in various diseases. However, its prognostic utility in decompensated liver cirrhosis (DLC) remains underexplored. This study aimed to investigate the association between SIRI and the risk of short-term (3 and 6 months) all-cause mortality in DLC patients.Methods: A total of 926 eligible patients with DLC from diverse etiologies was included in this study. In the initial cohort, the predictive accuracy of SIRI was evaluated using receiver operating characteristic (ROC) curve analysis. Patients were categorized into high- and low-SIRI groups based on the Youden index. Multivariable logistic regression analysis was employed to evaluate the independent association between SIRI and all-cause mortality. Restricted cubic spline (RCS) analysis was utilized to visualize the relationship between the continuous variable SIRI and mortality risk. These findings were validated in a validation cohort.Results: The initial cohort had mortality rates of 8.8% and 11.6% at 3 and 6 months, respectively. The SIRI level was significantly higher in the deceased group compared to the survival group. At both time points, SIRI was an independent indicator of all-cause mortality. RCS analysis demonstrated the risk of the risk of increased with an increase in SIRI value. The Validation cohort validated the independent association between higher SIRI levels and lower short-term all-cause mortality.Conclusion: This study’s findings underscore the prognostic value of SIRI in DLC patients, indicating that higher SIRI levels are significantly associated with short-term adverse outcomes.Keywords: decompensated liver cirrhosis, systemic inflammation response index, prognosis, all-cause mortality